Fenomena Sosial Anak Punk di Kota Padangsidimpuan - Amran, Ali (Hikmah, 2023)
AbstractThe social phenomenon of the Padangsidimpuan City punk community is an important fact to discuss, related to the existence and social behavior of the punk community in everyday interactions. It is hoped that the results of the study can contribute to the development of science in particular, as well as society in general regarding the behavior of punk children's community life. The results of the study show that the social fact of the existence of a community of punk children in Padangsidimpuan City is a real thing and exists in society. They have distinctive clothing characteristics, their activities are filled with gatherings and busking and do not have a fixed place so they are closer to wild children. However, they also carried out positive activities, namely volunteering for natural disasters in the city of Padangsidimpuan, one of which was the flash flood disaster that hit the city of Padangsidimpuan. The social behavior of punk children in Padangsidimpuan City is in fact a group of teenagers who dress in unusual ways. Then gather in the market center of Padangsidimpuan City and always play musical instruments made by themselves while singing in front of the evening snack visitors.AbstrakFenomena sosial komunitas anak punk Kota Padangsidimpuan suatu fakta yang penting dibahas, terkait dengan eksistensi dan perilaku sosial komunitas anak punk dalam pergaulan sehari-hari. hasil kajian diharapkan dapat memberikan kontribusi bagi perkembangan ilmu pengetahuan pada khususnya, maupun pada masyarakat pada umumnya mengenai perilaku kehidupan komunitas anak punk. Hasil kajian diketahui bahwa fakta sosial keberadaan komuntas anak punk di Kota Padangsidimpuan merupakan hal yang nyata dan eksis di dalam masyarakat. Mereka memiliki ciri pakaian yang khas, kegiatan mereka isi dengan kumpul-kumpul dan mengamen dan tidak memiliki tempat yang tetap sehingga lebih dekat kepada anak yang liar. Namun mereka juga melakukan kegiatan yang positif yakni ikut menjadi relawan dalam bencana alam di dalam kota Padangsidimpuan, salah satunya bencana banjir bandang yang menimpa kota Padangsidimpuan. Perilaku sosial anak punk yang ada di Kota Padangsidimpuan pada kenyataannya adalah kumpulan anak remaja yang berpakaian secara tidak biasa modelnya. Kemudian berkumpul di pusat pasar Kota Padangsidimpuan dan selalu memainkan alat musik yang dibuat sendiri sambil bernyanyi di depan pengunjung jajanan malam hari.